Ultrasound elastography score and strain index in different parathyroid lesions. Issue 12 (December 2019) - Cakir, Bekir; Cuhaci Seyrek, F Neslihan; Topaloglu, Oya; Ozdemir, Didem; Dirikoc, Ahmet; Aydin, Cevdet; Polat, Sefika Burcak; Ogmen, Berna Evranos; Tam, Ali Abbas; Baser, Husniye; Kilic Yazgan, Aylin; Kilic, Mehmet; et al.
Abstract : Background: Despite significant improvement in imaging quality and advanced scientific knowledge, it may still sometimes be difficult to distinguish different parathyroid lesions. The aims of this prospective study were to evaluate parathyroid lesions with ultrasound elastography and to determine whether strain index can help to differentiate parathyroid lesions. Methods: Patients with biochemically confirmed hyperparathyroidism and localised parathyroid lesions in ultrasonography were included. All patients underwent B-mode US and USE examination. Ultrasound elastography scores and strain index of lesions were determined. Strain index was defined as the ratio of strain of the thyroid parenchyma to the strain of the parathyroid lesion. Results: Data of 245 lesions of 230 patients were analysed. Histopathologically, there were 202 (82.45%) parathyroid adenomas, 26 (10.61%) atypical parathyroid adenomas, and 17 (6.94%) cases of parathyroid hyperplasia. Median serum Ca was significantly higher in atypical parathyroid adenoma patients than parathyroid hyperplasia patients ( P = 0.019) and median PTH was significantly higher in APA compared to PA patients ( P < 0.001). In 221 (90.2%) of the parathyroid lesions, USE score was 1 or 2. The median SI of atypical parathyroid adenomas was significantly higher than parathyroid adenomas and hyperplasia lesions (1.5 (0.56–4.86), 1.01 (0.21–8.43) and 0.91 (0.26–2.02), respectively, P = 0.003). Conclusion: Our study revealed that SI of parathyroid lesions as well as serum calcium, parathyroid hormone levels, and B-mode US features may help to predict the atypical parathyroid adenoma. Ultrasound elastography can be used to differentiate among parathyroid lesions and guide a surgical approach.